Pengaruh Rembesan Pada Kuat Geser Tanah Jenuh Sebagian: The Ifluence Of Water Infiltration To Shear Strength Of Unsaturated Soil - Gayuh Aji Prasetyaningtiyas; Kuswaji Dwi Priyono; Muhammad Najib Azhom; Muhammad Eryan Anindyaputra (​Institute for Researches and Community Services Universitas Muhammadiyah Palangkaraya, 2023)
This study aims to understand the interaction of engineering properties of unsaturated soil subjected to rainfall infiltration. It influences the variable of soil shear strength along with the alter of soil water content. A series of suction test was subjected to the silty sand layer, then the result was correlated with the change of soul degree saturation. The correlation then was implemented in soil water characteristic curve. A Bishop method was applied in this study to predict soil shear strength (τff) in variance of soil water content. Meanwhile, other samples from exiting condition were prepared. The samples were taken in rainy season and subjected shear strength test. The results then compared with the calculation of shear strength prediction by soil water characteristic curve. The research shows any high similarity between the prediction and the shear strength test value. Any change of shear strength value in prediction approach particularly was affected by the change of φb and X. The change of both parameters impacted to internal shear angle (φ’) thus, the infiltration mainly affected to the soil with low shear strength internal angle. This study is applicable for an area with unstable slope affected by rainfall infiltration such as landslide area